Generative and vegetative traits of the 'Granny Smith' apple grown under an anti-insect photoselective red net - Jemrić, Tomislav (Array, 2021)
Anti-insect photoselective nets present a new technology that combines light manipulation and pest protection in orchards. In this study, the effect of the anti-insect photoselective red net on the generative and vegetative traits was studied in an apple orchard near the city of Zadar, Croatia. 'Granny Smith' apples were grown on M9 rootstock and raised as slender spindles. The experiment consisted of two treatments: the trees covered with the red photoselective anti-insect nets (AGRITECH S. r. l., Eboli, Italy; mesh size of 2.4 × 4.8 mm) and uncovered trees as control. Yield, percentage of fruit with diameter >70 mm and fruit mass were not significantly different between treatments. L* color value was higher on fruit skin grown under the red net, and there was no significant difference in other color values (a*, b*, C* and h°). Soluble solids concentration (SSC) and total flavonoid content were significantly lower in fruit grown under red net than in control, and there was no significant difference in titratable acidity (TA), SSC/TA ratio, starch degradation and Streif maturity index. Red net proved to be effective against fruit red blush development (undesirable trait for 'Granny Smith' apple) and sunburn damage occurrence.